The Relationship Between Atherosclerotic Risk Factors and Coronary Artery Disease in Coronary Artery Ectasia - Mesut Keçebaş; Feyzullah Beşli; Serhat Çalışkan; et al. (Düzce Tıp Fakültesi Dergisi, 2015)
Aim: Coronary artery ectasia (CAE)is described as the dilatation of all or a portion of the coronary arteries by 1.5 times or more wider than the diameter of adjacent normal coronary artery segment. The incidence of CAE varies between 1.5 to 5%. Although the etiology of CAE has not been enlightened, it is generally considered to be a variant of coronary atherosclerosis. In our study, the association between atherosclerotic risk factors and coronary artery disease in patients with coronary artery ectasia was investigated. Methods: Between January 2008 - May 2012 , 5595 patients were screened retrospectively. Atherosclerotic risk factors were determined in all patients. Patients were grouped as the CAE with coronary artery disease (CAD) and the CAE who had no CAD. Results: CAE was diagnosed in 135 (2.4%) patients. The mean age was 62.2 years and 81.5% were male. 71.1% of the patients had CAD. In CAE patients with CAD, diabetes mellitus (DM) and hypertension (HT) was significantly higher in frequency than CAE patients without CAD. In logistic regression analysis, the presence of DM was increased the risk of CAD 2.59-fold, HT was increased the risk of CAD 3,39-fold. Between the two groups there was no significant difference for other atherosclerotic risk factors. Right coronary arteries were the most common vascular involvement (45.9%). Conclusion: In our study, the frequency of CAE was determined as 2.4%. DM and HT which are well-known risk factors for CAD, were seen more frequently in CAE patients with CAD.